Exploratory Factor Analysis of Financial Literacy in the Malaysian Context - Julaina Baistaman; Farahiyah Akmal Mat Nawi; Wan Masnieza Wan Mustapha; Mazlina Mamat (Proceedings, 2022)
Financial literacy has become one of the most important factors in personal financial management. Low financial literacy among Malaysians is an issue that leads to various problems such as bankruptcy, poor financial planning, inability to save for emergencies, and many more. This study aims to validate the measurement model for a Financial Literacy construct. Generally, the Exploratory Factor Analysis (EFA) is required to expose the appropriate items for use in research instruments. Thus, this study takes steps to develop and validate the instrument of financial literacy in the Malaysian context. This study adopted a cross-sectional research design, with data collected from 100 school teachers in the state of Kelantan, Malaysia. Items with a 10-interval scale were used. Using the Principal Component extraction method with Varimax Rotation, the researchers performed the EFA procedure on construct elements using SPSS software. Bartlett’s Test of Sphericity and the Kaiser–Meyer–Olkin (KMO) sampling adequacy were also performed. Cronbach’s alpha was used to test the reliability of the retained items. The items of financial literacy initially consist of 15 items. Based on the factor analysis, this study finalized the instrument of 11 financial literacy items, yielding three dimensions, i.e., numeracy (four items), time money value (four items), and inflation (three items). This study explained in detail the procedures for carrying out EFA analysis for the Financial Literacy construct. Due to the limited knowledge regarding the dimensions of the Financial Literacy construct, this study adds an important survey instrument to the literature that will help to measure financial literacy dimensions.